LPIC-1 Linux administrator (101-500) - Pezet, Don; Bryan, Wes (Packt Publishing, 2024)
The course begins by introducing you to the basics of Linux installation, ensuring you're well-equipped to set up Linux on both physical and virtual machines. It takes you through hardware detection and configuration, making sure your system is optimized for performance. You'll learn about the Linux boot process and how to configure GRUB, providing the knowledge needed to troubleshoot boot issues and understand system startup. The course focuses on the Linux shell, where you'll gain skills in managing processes and execution priorities, essential for maintaining a smooth and efficient system. Editing files with nano and vi is covered in detail, along with customizing the bash environment to streamline your workflow. You'll become proficient in managing files, redirecting data, and using powerful tools like grep to filter output, enhancing your day-to-day Linux administration tasks. The course wraps up by delving into advanced topics such as file permissions, ACLs, managing software with dpkg, apt, rpm, and yum, and understanding systemd for service management. Through practical exercises, you'll learn how to maintain filesystem health, manage disk utilization, and handle removable media, equipping you with the skills to manage Linux systems effectively. What you will learn Install Linux on VMs and hardware Detect and configure system hardware Manage boot processes and GRUB Utilize the Linux shell effectively Customize and optimize bash Handle file permissions and ownership Audience This course is ideal for aspiring system administrators, IT professionals, and tech enthusiasts looking to gain or enhance their Linux administration skills. Basic computer literacy and familiarity with operating systems are recommended to get the most out of this course. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Don Pezet: Don Pezet, with over 25 years in IT, brings rich experience from his time as a field engineer in finance and insurance, supporting networks globally. A Linux enthusiast, he's skilled in Red Hat and Ubuntu, and has a long-standing connection with macOS and Apple products since the mid-90s. For the last 15 years, Don has dedicated himself to IT education, co-founding ITProTV in 2012 to provide top-tier IT training. As ACI Learning's CPO, he continues to deliver innovative training to IT professionals. His credentials include Microsoft MCSE, Amazon ACSA, Cisco CCNP, LPI LPIC-2, PMI PMP, and several CompTIA certifications like A+, Network+, Security+, and Linux+. Wes Bryan: Wes Bryan embarked on his IT career path in 2009, initially as a mentored learning instructor, and later transitioning into a technical IT instructor. His exceptional teaching skills were recognized with three global teaching awards for 'Global Technical Instructor' during his early teaching years. Wes has made notable contributions as a member of the CIN (CompTIA Instructor Network) Advisory Board and the Board of Directors for CompTIA AITP (Association of Information Technology Professionals). Certifications: CompTIA A+, Network+, Security+, Server+, Cloud+, CySA+; MCSA; MTA; MCTS; MCP; MS; MCT.
Online resource; title from title details screen (O'Reilly, viewed March 4, 2024)
Keywords: Linux -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet